2017
DOI: 10.1007/s00737-017-0729-6
|View full text |Cite
|
Sign up to set email alerts
|

Preventing traumatic childbirth experiences: 2192 women’s perceptions and views

Abstract: The purpose of this study is to explore and quantify perceptions and experiences of women with a traumatic childbirth experience in order to identify areas for prevention and to help midwives and obstetricians improve woman-centered care. A retrospective survey was conducted online among 2192 women with a self-reported traumatic childbirth experience. Women were recruited in March 2016 through social media, including specific parent support groups. They filled out a 35-item questionnaire of which the most impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
132
2
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(188 citation statements)
references
References 18 publications
17
132
2
16
Order By: Relevance
“…In the present study, a significant relation was observed between satisfaction with delivery (p<0,001), perceived support during and after delivery (p=0,004) and infant status with PTSD following childbirth. Similar to the present study, other studies also reported the significant relation between delivery experiences and PTSD following childbirth [18,19]. In the study conducted by Dekel et al [20], negative experience of delivery was considered as the most important predictor of PTSD following childbirth.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the present study, a significant relation was observed between satisfaction with delivery (p<0,001), perceived support during and after delivery (p=0,004) and infant status with PTSD following childbirth. Similar to the present study, other studies also reported the significant relation between delivery experiences and PTSD following childbirth [18,19]. In the study conducted by Dekel et al [20], negative experience of delivery was considered as the most important predictor of PTSD following childbirth.…”
Section: Discussionsupporting
confidence: 78%
“…In the study conducted by Dekel et al [20], negative experience of delivery was considered as the most important predictor of PTSD following childbirth. In the study of Hollander et al [19] emotional and practical support by the medical team during labor was associated with decreased possibility of PTSD following childbirth and according to Simpson et al [21], low quality of the caregivers interactions during labor was reported as one of the most important risk factors for experiencing traumatic birth. In general, social support has an important role in decreasing stress and other mental problems following childbirth [22].…”
Section: Discussionmentioning
confidence: 99%
“…Further research will have to clarify which specific types of intervention or aspects of continuous support are effective in preventing a traumatic birth experience, but more direct support and attention to birthing women and their experience of birth could perhaps be one of them. A forthcoming study shows that women attribute their traumatic childbirth experience to a lack or loss of control, to suboptimal communication with health practitioners, and to too little practical and emotional support. Consequently, awareness of these factors among health practitioners could lead to a different role during labor and consequently to fewer traumatic events.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity for a midwife to empathically engage with women is essential for the provision of compassionate care, and to facilitate effective communication throughout the perinatal period. A recent survey in the Netherlands highlighted the importance of communication and clear, supportive interactions from healthcare providers in reducing the likelihood that birth was perceived as traumatic by new mothers (Hollander et al, 2017). Recent National Health Service (NHS) guidance in England plans for a system providing women and their families with greater continuity of care to facilitate the provision of empathic, woman-centred and quality care (NHS England, 2016).…”
Section: Discussionmentioning
confidence: 99%